METODE PEMBELAJARAN AQIDAH PADA MAN BANDA ACEH 1 - Syukri Syukri (Kalam: Jurnal Agama dan Sosial Humaniora, 2017)
Focus problem in this research is How many are the ranges of learning methods for Aqidah course at MAN 1 Banda Aceh? And whether the implementation of a variety of learning methods for Aqidah at Banda Aceh MAN 1 in accordance with the documentation for RPP? This research is a qualitative research. The technique of data collection conducted i.e., interview, observation and documentation that is used by the method of triangulation. Data analysis using models, Miles and Huberman. The results of this study indicates that the spectrum of learning methods for Aqidah course at Banda Aceh 1 MAN is carried out using the method of group discussion, faqs, inkuiri, lectures, group work, exercises and reward. As for the method to run in the learning for Aqidah course in Banda Aceh MAN 1 there are consistent with the RPP and there is also inconsistent with the RPP.